(untitled) (Scientific Journal of Research Studies in Future Management, 2023)
Although the importance of leadership for innovation processes has been confirmed, the knowledge of the relationship between leadership styles and the level of innovation in work teams is still limited; Therefore, the present study was conducted with the aim of investigating charismatic leadership and its effects on work team innovation behavior. The following article is a review research of descriptive-analytical type. The method of collecting information in the current research is a library. Based on the results of this study, it can be said that in order to produce creativity and increase innovation, charismatic leadership must be able to create changes in the organization and lead from the existing situation to a new stage and form a team culture according to the conditions and requirements, because in this type Culture emphasizes invention, discovery and innovation. Perhaps one of the most important factors facilitating the ability of creativity and innovation in the organization is the appropriate structure and organization in accordance with the desired goals, which in this context is the biological or organic structure, the appropriate structure for creativity and innovation in the organization.